Knowledge retention level among pre-school teachers in conducting pre-school children vision screening - Tan, Xuan Li; Rokiah Omar,; Victor Feizal Knight, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Certain public service pre-school teachers have been trained as vision screeners of children. However, there are no studies that assessed the knowledge and skills retention of these screeners. This study determines the level of knowledge retention among pre-school teachers who have been trained to perform vision screening on children. In 2013, 180 KEMAS pre-school teachers were recruited in a vision screening training which included both theory and practical sessions. Teachers were assessed through a theory test which comprised of 15 questions, firstly a category on the preparations needed for vision screening and secondly on the implementation of vision screening. They were then asked to conduct pre-school vision screening annually at their working premises. In 2016, 136 teachers who had been involved in the earlier program were recruited as subjects in this study. All these subjects answered the same set of theory test questions used in 2013. The Student’s t-test result indicated that the mean theory test scores obtained by the pre-school teachers in 2013 (84.3 ± 7.8) differed significantly with the mean scores obtained in 2016 (67.5 ± 11.3) (p < 0.001). The mean scores in 2013 for questions in the first and second categories were 4.5 and 4.4, decreasing to 4.2 and 3.7 in 2016. The knowledge level of pre-school teachers thus decreased with time and this effect was found significant after 3 years. There is therefore a need to conduct re-certification training, so that the screening conducted by these pre-school teachers remains effective and in accordance with established standards.